2020
DOI: 10.1017/s0021932020000620
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women’s decisions regarding birth planning in a rural setting in Kenya and their implications for family planning programmes

Abstract: Evidence suggests that socio-cultural barriers that limit the ability of women in sub-Saharan Africa to make decisions regarding contraceptive use and childbearing contribute to the slow uptake of contraception in this region. This paper explores factors influencing women’s decisions regarding contraceptive uptake, switching and discontinuation, and the implications of those decisions for family planning programmes. Data were from in-depth interviews that were conducted in 2018 with 42 women who participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although ‘don’t know’ responses were reclassified as disapproval, this is unlikely to account for the contrast—most past users who gave ‘don’t know’ responses were also dissatisfied with the method. Qualitative research suggested that clandestine use of contraception is common in Homa Bay because of hostility or indifference of the partner but no similar evidence is available for Nairobi [ 23 ]. It is also the case that polygyny is much more common in Homa Bay (25%) than in Nairobi (5%) and the existence of co-wives may create social distance between partners and reduce discussion of matters such as contraception [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ‘don’t know’ responses were reclassified as disapproval, this is unlikely to account for the contrast—most past users who gave ‘don’t know’ responses were also dissatisfied with the method. Qualitative research suggested that clandestine use of contraception is common in Homa Bay because of hostility or indifference of the partner but no similar evidence is available for Nairobi [ 23 ]. It is also the case that polygyny is much more common in Homa Bay (25%) than in Nairobi (5%) and the existence of co-wives may create social distance between partners and reduce discussion of matters such as contraception [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The population of Homa Bay is predominantly composed of the Luo ethnic group and the main occupation is subsistence agriculture and fishing. The county has a high fertility rate of 5.2 and a high unmet need for family planning (26%), with less than half (47%) of married women using contraception [ 23 ]. It also has a much higher level of HIV infection than Nairobi (20% and 4%, respectively) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%